2014
DOI: 10.1007/s11426-014-5225-5
|View full text |Cite
|
Sign up to set email alerts
|

Tightening up the structure, lighting up the pathway: application of molecular constraints and light to manipulate protein folding, self-assembly and function

Abstract: Chemical cross-linking provides an effective avenue to reduce the conformational entropy of polypeptide chains and hence has become a popular method to induce or force structural formation in peptides and proteins. Recently, other types of molecular constraints, especially photoresponsive linkers and functional groups, have also found increased use in a wide variety of applications. Herein, we provide a concise review of using various forms of molecular strategies to constrain proteins, thereby stabilizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 152 publications
0
8
0
Order By: Relevance
“…One promising and practical approach of site-specifically increasing the local mass density and hence, the degree of crowding, is to insert a specific construct to the desired molecular location. Indeed, several studies have taken advantage of recent developments in peptide chemistry and protein design and used molecular cross-linkers, 20 such as azobenzene and m -xylene, to manipulate molecular crowding in a site-specific manner. For example, in order to mimic the crowded environment within which α-helix folding takes place in proteins, Hamm and coworkers 21 employed a photo-switchable azobenzene moiety to simultaneously serve as a photo-trigger of the folding kinetics of an alanine-rich peptide and a structural constraint to reduce its conformational flexibility.…”
Section: Nano-crowding Arising From Molecular Constraintsmentioning
confidence: 99%
“…One promising and practical approach of site-specifically increasing the local mass density and hence, the degree of crowding, is to insert a specific construct to the desired molecular location. Indeed, several studies have taken advantage of recent developments in peptide chemistry and protein design and used molecular cross-linkers, 20 such as azobenzene and m -xylene, to manipulate molecular crowding in a site-specific manner. For example, in order to mimic the crowded environment within which α-helix folding takes place in proteins, Hamm and coworkers 21 employed a photo-switchable azobenzene moiety to simultaneously serve as a photo-trigger of the folding kinetics of an alanine-rich peptide and a structural constraint to reduce its conformational flexibility.…”
Section: Nano-crowding Arising From Molecular Constraintsmentioning
confidence: 99%
“…It is also clear that in order to move the field forward, new experimental methods that can offer better time and structural resolution are needed. For example, several techniques, including laser‐induced temperature‐jump, laser‐induced pH‐jump, and phototriggering based on cleavage of a tetrazine or a photocage, can potentially be used to induce or initiate a membrane protein folding process on the nanosecond or microsecond timescale. In addition, by using a photoresponsive structural constraint, it is possible to initiate a folding or unfolding process from a well‐selected conformational state.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…67−75 While the frictional effect arising from the solvent is relatively easy to quantify, that arising from a protein's backbone and side chains is more difficult to characterize. In a recent study, Markiewicz et al 76,77 showed that it is possible to estimate the magnitude of internal friction arising from a short structural segment by selectively increasing the local mass density of a protein via addition of a cross-linker. Specifically, they demonstrated the feasibility of this approach by characterizing the stability and folding/unfolding kinetics of a crosslinked variant of the mini-protein Trp-cage, 78 4-8-CL-Trp-cage, where an m-xylene cross-linker 79 is anchored to the protein's αhelix between positions 4 and 8 (Figure 8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Protein folding is subject to both external (i.e., from solvent) and internal (i.e., from backbone and side chains) frictional forces. While the frictional effect arising from the solvent is relatively easy to quantify, that arising from a protein’s backbone and side chains is more difficult to characterize. In a recent study, Markiewicz et al , showed that it is possible to estimate the magnitude of internal friction arising from a short structural segment by selectively increasing the local mass density of a protein via addition of a cross-linker. Specifically, they demonstrated the feasibility of this approach by characterizing the stability and folding/unfolding kinetics of a cross-linked variant of the mini-protein Trp-cage, 4-8-CL-Trp-cage, where an m -xylene cross-linker is anchored to the protein’s α-helix between positions 4 and 8 (Figure ).…”
Section: Resultsmentioning
confidence: 99%